The Biomedical Aspects of Autism - Kong, MD, Xuejun (North American Journal of Medicine and Science, 2008)
Over the last several decades, autism has become an increasingly prevalent developmental disorder that has received attention both in the medical and public communities. In the 1960’s, the incidence was 1/10,000 which has since increased to 1/150 from 1991 to 1997. In 2007, more children were diagnosed with autism compared with diseases like cancer, diabetes, and AIDS combined. On average a new case of Autism is diagnosed every 20 minutes in the USA.1 Autism costs more than $90 billion a year nationwide, however, the research grant available for autism accounts only to 0.3% of the total NIH funding, which is still lower than what is available for other less common disorders. Autism is more of a clinical syndrome than a disease. It is a behaviorally defined disorder.2 It was first described by Leo Kanner in 1943,3 and a milder form was described by a German doctor Hans Aspergers, now known as Asperger Syndrome.4 Since then, many subtypes have been proposed and its cause, diagnosis and treatments remain controversial. This clinical syndrome is characterized by impaired social interaction, qualitative impairment in communication and restrictive, repetitive and stereotypic behaviors.